Asia’s MDB Donor Project Fraud Epidemic - Risk Management Impacts Using an Expert Panel - Prof Dr Paul James, (Journal of Management Research, 2025)
Multilateral development banks (MDBs) finance complex Asian projects, but government and local donor personnel often neglect established protocols and assessment procedures. Furthermore, MDB complaint mechanisms lack local visibility due to centralized management and limited cross-border oversight, focusing mainly on mitigating donor risk. This research employed the Delphi technique to conduct a qualitative evaluation of fraud management practices in three MDB-funded infrastructure projects across various Asian countries. The experts contained within an “expert panel” constituted a sample from a closed population of borrower stakeholders, relating to complex construction projects. The pool of experts were chosen through a snowball sampling process where each expert was corroborated independently, whilst adhering to anonymity procedures. The independent expert panel was employed to generate consensus, through an iterative process, and controlled, by independent online feedback. The modified Delphi design entailed 3 review iterations. The outcome reflected 11 main themes, and 28 sub-themes after iteration 3. The main themes underwent further assessment and were reduced to 4 main themes, corroborated through iteration 3 outcomes. These were Donor Governance; Stakeholder Issues; Project Fraud Risk Management; and Project Resilience. The study outcomes showed that donor governance is reduced in Asia, most often by government agency management interventions, who conduct fraud on projects with collusive elements from the PMC whilst undertaking coercion measures to hide and reinforce fraudulent behaviour. There is little or no project risk management conducted showing that the donor’s do not conduct project risk management to protect their project assets in a loose laissez-faire management style indicating political interference and fear.